The Geomorphology of Greece - Konstantinos Tsanakas; Karymbalis, Efthimios; Griva, Diamantina; Valkanou, Kanella; Batzakis, Dimitrios-Vasileios; Vassilakis, Emmanuel; Konsolaki, Aliki; Gaki-Papanastassiou, Kalliopi (Journal of Maps, 2025)
The study presents a geomorphological overview of Greece at a 1:1,000,000 scale, marking the first national cartographic synthesis effort to interpret geological and geomorphological factors shaping the country's landscape. The geomorphological map was developed through a literature review of prior studies at varying scales and semi-automated GIS techniques. High-resolution topographic data and 1:50,000 geological maps were integrated into a spatial geodatabase. Secondary layers, including a hillshade map, slope-aspect map, and red relief image map, were created and combined with Google Earth imagery to delineate landforms. These were categorized by primary formative processes into structural, fluvial, gravity-induced, coastal, karst, volcanic, glacial and periglacial. Additional maps and tables were produced, detailing topographic parameters, geotectonic setting, and climatic regime. The results highlight Greece's diverse geomorphological environments, shaped by active tectonics and surface processes. The map represents recent geomorphological advancements and serves as a management tool for stakeholders and a reference for interdisciplinary research.